2022
DOI: 10.1177/00219096221141338
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral Land Rights and Environmental Resource Governance and Sustainability along Ethiopia–Kenya border

Abstract: Past studies mainly focused on the effects of the lack of a pastoral land tenure security system. There is scarcity of evidence regarding the effects of pastoral land tenure insecurity in the context of cross-border environmental resource governance and sustainability that the present study attempted to contribute. The main objective of this study is therefore to assess how far the state land tenure system has impacted environmental resource governance and sustainability along the Ethiopia–Kenya border. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Alemu et al [6] reported that the highest barley yield (2.2 t ha -1 ) in Ethiopia was achieved by 1.65 t ha -1 of liming and 30 kg ha -1 of P fertilizer. Applying 4.47 t ha -1 of lime to acidic soil in Ethiopia significantly reduced exchangeable acidity (Al 3+ and H + ) from 1.90 to 0.92 cmolc kg -1 at first season, increased available P from 1.48 mg kg -1 to 2.38 mg kg -1 , increased exchangeable calcium (Ca) from 4.50 to 6.65 cmolc kg -1 , and increased the cation exchange capacity (CEC) of the soil from 17.56 to 20.66 cmolc kg -1 [16]. Liming had a significant effect on the weight of 1,000 corn kernels, available P, Mg 2+ , increasing soil pH, reducing exchangeable Al 3+ , and soil acidity in acidic soil in Kebele [17].…”
Section: Introductionmentioning
confidence: 99%
“…Alemu et al [6] reported that the highest barley yield (2.2 t ha -1 ) in Ethiopia was achieved by 1.65 t ha -1 of liming and 30 kg ha -1 of P fertilizer. Applying 4.47 t ha -1 of lime to acidic soil in Ethiopia significantly reduced exchangeable acidity (Al 3+ and H + ) from 1.90 to 0.92 cmolc kg -1 at first season, increased available P from 1.48 mg kg -1 to 2.38 mg kg -1 , increased exchangeable calcium (Ca) from 4.50 to 6.65 cmolc kg -1 , and increased the cation exchange capacity (CEC) of the soil from 17.56 to 20.66 cmolc kg -1 [16]. Liming had a significant effect on the weight of 1,000 corn kernels, available P, Mg 2+ , increasing soil pH, reducing exchangeable Al 3+ , and soil acidity in acidic soil in Kebele [17].…”
Section: Introductionmentioning
confidence: 99%